2014
DOI: 10.1111/jpc.12652
|View full text |Cite
|
Sign up to set email alerts
|

Oral vitamin B12 treatment is effective for children with nutritional vitamin B12 deficiency

Abstract: Data from this study indicate that oral vit-B12 (1000 μg) for 4 months is effective, giving clinicians more choice, for treatment of children with nutritional vit-B12 deficiency. However, despite this high dose, lower levels were achieved in older children indicating the necessity of dosage adjustment in accordance with body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 15 publications
0
27
0
9
Order By: Relevance
“…A study among 47 vitB12-deficient children showed an effective response with 1,000 g oral vitB12 as intermittent therapy for 4 months. 7 A few other small studies and case reports among children also supported oral vitB12 as a treatment option, even in cases of selective vitB12 malabsorption. 8,9 Since our study included children aged 6 months-18 years, instead of using a fixed-dose vitB12 formulation for all, we used a daily dose per unit body weight of methylcobalamin.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A study among 47 vitB12-deficient children showed an effective response with 1,000 g oral vitB12 as intermittent therapy for 4 months. 7 A few other small studies and case reports among children also supported oral vitB12 as a treatment option, even in cases of selective vitB12 malabsorption. 8,9 Since our study included children aged 6 months-18 years, instead of using a fixed-dose vitB12 formulation for all, we used a daily dose per unit body weight of methylcobalamin.…”
Section: Discussionmentioning
confidence: 92%
“…A limited number of pediatric studies also have documented an adequate response. A study among 47 vitB12‐deficient children showed an effective response with 1,000 μg oral vitB12 as intermittent therapy for 4 months . A few other small studies and case reports among children also supported oral vitB12 as a treatment option, even in cases of selective vitB12 malabsorption …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two forms of vitamin B 12 are usually used, cyanocobalamin (Cnbl) and hydroxocobalamin (Hdrx). The route of administration of vitamin B 12 therapies has been extensively studied in young [21], adult and elderly patients [22][23][24].…”
mentioning
confidence: 99%